Knowledge, education and employability of Nigerian graduates (2016)
This paper accentuates the fact and reality that there are many qualified graduates in Nigeria without jobs. Although governments, institutions of learning and organisations are responding to this social problem in myriad of ways, there is need to ask why the proposed solutions seem not to be producing the expected results. An argument that this position holds is that human capacity building has enormous power to solve the problem of unemployment when individual talents are allowed to be expressed rather than put prospective workers on the guise that some courses are more professional and profitable than others. The non-formal education possibilities, therefore, portend a more realistic solution to the problem of unemployment by collective appreciation of human being for who they are rather than make them serve as materials and machine for consumption only